Xueshuantong Improves Functions of Lymphatic Ducts and Modulates Inflammatory Responses in Alzheimer’s Disease Mice - Zheng, Rui; Huang, Yang-mei; Zhou, Qiang (Frontiers in Pharmacology, 2021)
Recent studies have revealed significant contributions of lymphatic vessels (LVs) to vital functions of the brain, especially related to clearance of waste from the brain and immune responses in the brain. These studies collectively indicate that enhancing the functions of LVs may improve brain functions during brain aging and in Alzheimer’s disease (AD) where LV functions are impaired. However, it is currently unknown whether this enhancement can be achieved using small molecules. We have previously shown that a widely used Chinese herbal medicine Xueshuantong (XST) significantly improves functions and reduces pathology in AD transgenic mice associated with elevated cerebral blood flow (CBF). Here we show that XST partially rescues deficits in lymphatic structures, improves clearance of amyloid-β (Aβ) from the brain, and reduces the inflammatory responses in the serum and brains of transgenic AD mice. In addition, we showed that this improvements in lymphatic system occurs independently of elevated CBF, suggesting independent modulation and limited interaction between blood circulation and lymphatic systems. Moreover, XST treatment leads to a significant increase in GLT-1 level, a significantly lower level of MMP-9 and restores AQP4 polarity in APP/PS1 mice. These results provide the basis for further exploration of XST to enhance or restore LV functions, which may be beneficial to treat neurodegenerative diseases or promote healthy aging.